BF3·Et2O-Mediated annulation of α-keto acids with aliphatic ketones for the synthesis of γ-hydroxy-butenolides and γ-alkylidene-butenolides. Issue 37 (25th August 2022) - Cheng, Zhenfeng; Gu, Qingyun; Xie, Yushan; Zhang, Yanan; Zeng, Xiaobao
Abstract : An efficient approach to divergently access γ-hydroxy-butenolides and γ-alkylidene-butenolides via annulation reaction of α-keto acids with simple aliphatic ketones is reported herein. Abstract : Annulation reaction of α-keto acids with cyclic or acyclic aliphatic ketones is reported herein to divergently access γ-hydroxy-butenolides and γ-alkylidene-butenolides depending on the amount of BF3 ·Et2 O. This protocol features good functional tolerance and ease of operation, to open a route to access butenolides via an annulation and dehydration process.